Antinomies of Progress. Notes on Adorno’s Critical Theory and the Concept of Progress in Our Time - Rensmann, Lars (Filosofia Morale/Moral Philosophy, 2024)
Today, the idea of progress is confronted with four distinct but interrelated challenges: global authoritarian regressions and democratic backsliding; the looming climate catastrophe; the partial dissolution of recognizable boundaries between human agency and artificial intelligence; and omnipresent forms of digital reproduction through which seemingly every human interaction is identified, measured, counted, objectified, and valorized. Turning especially to Adorno’s essay on “Progress,” I address these four steep challenges facing contemporary society and their meaning for (moral) progress from the perspective of Frankfurt School Critical Theory. Rather than resigning to a negative telos and the realistic threat of disaster, I propose a critical and dialectical notion of (both moral and social) progress that takes inspiration from Adorno’s work. It contains and upholds the possibility of genuine betterment, of averting catastrophe, and of redemption while critically reflecting on the conditions and societal trends towards destruction and what I call hyperreification. I argue that Adorno’s idea of progress continues to shed light on problems and antinomies in the contemporary age of unreason, recognizing both its entanglement in society and its critical qualities.